PERANCANGAN APLIKASI GRAVIDA MENGGUNAKAN METODE AGILE BERBASIS WEBSITE - Wafiq Azizah; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2025)
This research aims to design and develop the Gravida application using the website-based Agile method. This application is designed to help increase efficiency in monitoring daily activities carried out by gravida, such as examination schedules, exercise, diet, and many more that were previously done manually. With this research, gravida activity data can be managed centrally and provide information that is easily accessible to health workers and gravida itself. System testing is carried out using the blackbox testing method to ensure that each feature developed is functioning properly according to user needs. The result of this study show that gravida application is able to provide an efficient and effective solution in managing pregnancy-related information. With this, Gravida application is expected to be a solution for maternity clinics, especially at the Yustina Midwife clinic, in improving work efficiency and service quality to Gravida